Factors contributing to social cognition impairment in borderline personality disorder and schizophrenia. Issue 3 (30th October 2015) - Andreou, Christina; Kelm, Lea; Bierbrodt, Julia; Braun, Vivien; Lipp, Michael; Yassari, Amir H.; Moritz, Steffen
Abstract: Social cognition (SC) deficits have been described both in patients with schizophrenia and borderline personality disorder (BPD). However, while the former tend towards simplistic mental state attributions (undermentalizing), the latter are more likely to make overly complex mental state inferences (overmentalizing). Performance on complex SC tasks has been shown to correlate with neurocognitive ability, emotion perception, a history of trauma, and overconfidence in errors. However, it is unclear how these factors relate to different aspects of SC deficits. Aim of the present study was to examine the pathways of SC impairment by investigating performance profiles and their predictors comparatively in BPD and schizophrenia. Participants were 44 patients with BPD, 36 patients with schizophrenia, and 38 healthy controls. Undermentalizing and overmentalizing were assessed with an ecologically valid SC task. Patients with BPD exhibited increased overmentalizing, whereas patients with schizophrenia showed a more extensive deficit pattern, their main error type being undermentalizing. Overconfidence in errors was the most important predictor for overmentalizing, while undermentalizing depended mainly on verbal memory and emotion perception. Thus, BPD und schizophrenia exhibited different SC impairment patterns, and different types of SC errors were predicted by different factors. These findings have implications for the optimization of treatment approaches. Highlights: We investigated social cognition (SC) comparatively in schizophrenia and BPD. Patients with BPD exhibited increased overmentalizing. Patients with schizophrenia exhibited predominantly increased undermentalizing. The two different types of SC impairment were associated with different predictors.